Tobacco and betel nut use among school going adolescents of South Gujarat region, India: a cross sectional study - Pandya, Bharatkumar Balkrishna; Chaudhari, Upendrakumar Rameshbhai; Bhatt, Avirat A.; Thakor, Nilesh (International Journal of Contemporary Pediatrics, 2019)
Background: Adolescence period is very crucial in the life of an individual, when major physical, psychological and behavioral changes take place. Tobacco and Areca nut use among school going adolescent is becoming a major public health problem. Objective of this study was to determine the prevalence and pattern of smokeless tobacco and betel nut use among school going adolescents. Methods: The study was a cross sectional study. After taking the permission of principal of Government high schools of Vadodara and Surat city of Gujarat and consent of the parents of adolescents, 1107 adolescents were interviewed during March-April 2017. A self-administered questionnaire was used for data collection. Thus collected data was analyzed using SPSS 17 (Trial Version). Results: Age of the study students (total 1107) ranged from 10-19 years. (Mean age=14.61±2.85 years). Out of 1107 children 389 (35.1%) children had addiction. Prevalence of any type of addiction in girls and boys was 14.3% and 20.7% respectively. Tobacco prevalence was 13.4% and betel nut prevalence was 21.6%. Type of addiction and its association with gender was highly significant. All children addicted to tobacco using chewing form (gutkha) of tobacco. The mean age group of children who consume tobacco and betel nut was 16.13±1.32 years and 16.01±1.21 years respectively. Most common reasons among adolescents for starting addiction of tobacco and betel nut was to look mature (93.8%) followed by to look good (63.2%) and to refresh breathe (48.6%). Conclusions: High prevalence of tobacco and betel nut use among adolescents needs attention of parents, teachers and health officials.